The Usul-Vezin Relationship In Seyh Galib's Composed Poems - Oter, Serda Turkel; Yildirim, Ali (Selcuk Univ, Inst Turkish Studies, 2010)
In this study, after briefly Seyh Galib's life and Works mentioned, is shown and explained the known relations between the usul-vezin, which in this Works of Seyh Galib composed by verbal music forms called apart from religion.
Keywords: Seyh Galib; Usul-Vezin; Terennums; Repetition